Marie Antoinette fashionable queen or greedy royal? - Webb, Sarah Powers (North Mankato, Minnesota Capstone Press, 2015)
Details the life of Marie Antoinette from differing perspectives"--
Famous People
a gift from book africa
1 2 13 15
Keywords: Marie Antoinette -- Queen, consort of Louis XVI, King of France -- 1755-1793 -- Juvenile literature; Queens -- France -- Biography -- Juvenile literature